1983
DOI: 10.1111/j.1651-2227.1983.tb09710.x
|View full text |Cite
|
Sign up to set email alerts
|

Dyggve‐melchior‐clausen Dysplasia

Abstract: The results of light and electron microscopic examination and of biochemical proteoglycan studies of costochondral and iliac crest biopsies from a recently diagnosed case of Dyggve-Melchior-Clausen dysplasia are reported. At light microscopy of resting cartilage large lacunae containing clusters of five or more chondrocytes were seen in some areas. In the hyaline cartilage there were scattered fibrous foci but no mineralized areas. Electron microscopy revealed chondrocytes containing widened cisternae of rough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

1987
1987
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(2 citation statements)
references
References 15 publications
(6 reference statements)
0
1
0
1
Order By: Relevance
“…Histochemical analysis of iliac crest growth plates in patients with DMC syndrome has revealed that a defect in endochondral ossification may cause skeletal dysplasia [ 8 , 9 ]. Studies thus far have not evaluated the GH axis in patients with this syndrome, and the role of rGH therapy in this disorder has not been studied either.…”
Section: Discussionmentioning
confidence: 99%
“…Histochemical analysis of iliac crest growth plates in patients with DMC syndrome has revealed that a defect in endochondral ossification may cause skeletal dysplasia [ 8 , 9 ]. Studies thus far have not evaluated the GH axis in patients with this syndrome, and the role of rGH therapy in this disorder has not been studied either.…”
Section: Discussionmentioning
confidence: 99%
“…Η χάραξη της πρότυπης καμπύλης έγινε με τη μέτρηση της απορρόφησης πρότυπων διαλυμάτων Ν-ακετυλο-νευραμινικού ο ξέος όγκου 0,2 ml και συγκέντρωσης 10-60 \ig/ml. (238). Η κατανομή του μοριακού μεγέθους των ετεροττολυσακχαριτών, πριν και μετά από β-απόσπαση, προσδιορί στηκε με χρωματογραφία σε τρεις συνδεδεμένες μεταξύ τους, HPLC στήλες,μ-Bondagel Ε-500.…”
Section: β προσδιορισμός εξοζαμινώνunclassified